Design and test of powerful air-assisted sprayer for high stalk crops - Miao, Youyi; Chen, Xiao; Gong, Yan; Liu, Dejiang; Chen, Jian; Wang, Guo; Zhang, Xiao (Frontiers in Plant Science, 2023)
The canopies of high stalk crops, such as maize, intersect the rows at the later stages of growth, making conventional sprayers unable to enter the field for spraying. A powerful air-assisted spraying machine was designed. The sprayer structure, the design of air-assisted system and spraying system were presented. The air-assisted system was designed as an adjustable air-assisted deflector duct, enabling it to efficiently accommodate crops with different height. The spraying system consisted of strong air-assisted nozzles and high-pressure hydraulic nozzles, which could not only deliver the droplet to the remote distribution but also improve the droplet penetration. Field experiments for wind-field distribution and droplet distribution were conducted to verify the technical performance and working quality of powerful air-assisted sprayer. The experimental results showed that the wind field exhibited the capability to cover distances exceeding 50 metres. The wind field covered a concentrated space area and had a dominant position in the middle of the range near the bottom. Maize at all three heights had good coverage and deposition. The average coverage in the 30 to 60 metres range was more than 5%. The deposition at the bottom has a mean value of 1.6 μg cm-2.